The Importance of Administrative Committees in Training Course Preparation in Iraqi Handball Coaches - Kadhim, Hussein Abdullah; Hussain, Fouad Muttib (Journal of Physical Education, 2021)
The research aimed at preparing management and administration program for Iraqi handball coaches’ training course the problem of the research lies in lack of programs for academic training courses administration study that are designed especially for Iraqi handball coaches participating in such course held by the Iraqi handball federation. The researchers used the descriptive method on (64) individuals and applied the questionnaire on (13) committees. The data was collected and treated using SPSS to conclude a significant correlation between the knowledge of administrative committees and proficiency of holding training courses.